ANALISIS PERILAKU PREFERENSI DAN KEPUASAN KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN KOPI LIBERIKA DI KABUPATEN TANJUNG JABUNG BARAT - Fitri Handayani; Suandi Suandi; Rozaina Ningsih (Universitas Muara Bungo, 2026)
Coffee has become an inseparable part of the lifestyle of society, especially in Indonesia. One type of coffee that is widely favored is Liberica coffee. Liberika Tungkal Komposit Coffee (Libtukom) is a leading commodity of Tanjung Jabung Barat Regency, Jambi Province, which has the unique characteristic of growing on peatlands and has been designated as a cultivated variety by the Ministry of Agriculture. Tanjung Jabung Barat has become the center of Liberica coffee. Shop/café owners must not only be able to sell their products and services, but also need to have the ability to understand and comprehend consumer tastes, in order to remain competitive amid the increasingly growing coffee business world. Therefore, this paper needs to examine consumer behavior, preferences, satisfaction, and purchasing decisions.This study integrates literature from various sources including Fishbein's multi-attribute analysis, Conjoint analysis, and the Customer Satisfaction Index (CSI). The meta-analysis findings indicate that sensory attributes (taste, aroma, aftertaste, and thickness) are the dominant factors influencing consumer preferences, while price and packaging serve as secondary considerations. Consumers tend to repurchase and recommend products when they are satisfied. Consumer satisfaction has been proven to positively correlate with repurchase decisions. This research contributes to the development of coffee quality, which in turn influences preferences and plays an important role in driving purchasing decisions.